2011
DOI: 10.1039/c0cc02921a
|View full text |Cite
|
Sign up to set email alerts
|

Boronic acid building blocks: tools for self assembly

Abstract: Dynamic covalent functionality has been acknowledged as a powerful tool for the construction of organised architectures, the reversible nature thermodynamically facilitates self-control and self-correction. The use of boronic acids complexation with diols and their congeners has already shown great promise in realising and developing reversible boron-containing multicomponent systems with dynamic covalent functionality. The structure-directing potential has lead to the development of a variety of self-organisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
269
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(275 citation statements)
references
References 216 publications
2
269
0
4
Order By: Relevance
“…The head group of PI(4,5)P 2 contains phosphate and hydroxyl functionalities (see Figure 1a) that can be exploited for this purpose. For example, it is well established that ureas can form complementary hydrogen bonding interactions with phosphates (15)(16)(17)(18), while boronic acids have been successfully used for the molecular recognition of diols via the reversible formation of B-O covalent bonds (19,20). Thus, we designed a chemical receptor (PHDM) that utilizes ureas and boronic acids as recognition motifs (see Figure 1b).…”
Section: Design and Development Of A Chemical Receptor For Pi(45)pmentioning
confidence: 99%
“…The head group of PI(4,5)P 2 contains phosphate and hydroxyl functionalities (see Figure 1a) that can be exploited for this purpose. For example, it is well established that ureas can form complementary hydrogen bonding interactions with phosphates (15)(16)(17)(18), while boronic acids have been successfully used for the molecular recognition of diols via the reversible formation of B-O covalent bonds (19,20). Thus, we designed a chemical receptor (PHDM) that utilizes ureas and boronic acids as recognition motifs (see Figure 1b).…”
Section: Design and Development Of A Chemical Receptor For Pi(45)pmentioning
confidence: 99%
“…However, several factors such as mixing speed, temperature, pH, and the presence of boric acid on PGB-0 structure need to be controlled to minimize the by-product. Boric acid easily reacts with the other boric acid to produce boroxine (Nishiyabu et al, 2011). Our result demonstrated that PGB-0 inhibited cells growth of HER2 overexpressed-cancer cells and performed no effect on normal cells.…”
Section: Pgb-0 Decrease Her2 Expressionmentioning
confidence: 63%
“…The supramolecular polymer gel was sensitive to three different external stimuli and a rapid self-healing property based on boron-catechol interactions was demonstrated. Other research groups also developed artificial stimuli-responsive gels, including pHresponsive [29][30][31][32][33] and sugar-responsive [34] polymer gels via boric-catechol complexation for biomaterials applications. In this study, we present a pH-responsive self-healing hydrogel, inspired by adhesive mussel proteins, based on 3,4-dihydroxyphenethylamine(or dopamine)-conjugated polyaspartamide.…”
Section: Introductionmentioning
confidence: 99%